Finance and Inequality - Cihak, Martin (Staff Discussion Notes; Staff Discussion Notes, 2020)
The study examines empirical relationships between income inequality and three features of finance: depth (financial sector size relative to the economy), inclusion (access to and use of financial services by individuals and firms), and stability (absence of financial distress). Using new data covering a wide range of countries, the analysis finds that the financial sector can play a role in reducing inequality, complementing redistributive fiscal policy. By expanding the provision of financial services to low-income households and small businesses, it can serve as a powerful lever in helping create a more inclusive society but-if not well managed-it can amplify inequalities.